The Influence of Baby Spa Toward Growth and Development Rough and Smooth Motoric Babies, Age 3 – 12 Months in the Subdistrict Lapongkoda Disrict of Tempe Wajo Regency - Een Kurnaesih1 , Ariesty AR 2, Masriadi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. Baby Spa can fulfill three basic needs of babies that is physical needs biological needs,emotional needs, affection needs, stimulation needs. This baby massage contains touch substances such asaffection voice or talking, eyes contract, action and spa. Baby spa is also one of stimulation substances whichwill stimulate structure development as well as the function of working the cores in brain. This research aimsto analyze the influence of baby spa toward growth and development rough and smooth motoric babieswho have age 3 – 12 months in the subdistrict Lapongkoda disrict of Tempe Wajo regency. Material andMethods. The type of research used was an quasi experiment study design. The sampling method usessimple random sampling. The study was conducted in July – August 2019. The number of sampling was 32people. The population and research sample are babies in the subdistrict Lapongkoda disrict of Tempe Wajoregency. The data analysis technique used in this is T-test. Results. The result of research indicates that thereare influences of babies weight growth after doing baby spa p (0,000) <p (0.05), influences of developmentrough motoric after doing baby spa p (0,000) <p (0.05), influences of development smooth motoric afterdoing baby spa p (0,000) <p (0.05). Conclusion. These findings showed growth and development motoricbabies, age 3 – 12 months, can be improved by providing baby spa treatment. It is recommended that theEfforts that need to be considered for health workers are developing baby spa promotion and education aswell as baby massage to baby’s parents so that the needs regarding increasing baby’s motor growth anddevelopment can be met.